Let r(s) = -s3 + 8*s2 + 9*s + 4. Suppose -33 = -4*g - 9. Let z = 3 + g. Let v be r(z). Solve 0 = -v*h + 9*h for h.

0

Let r be ((-10)/(-8))/(416). Let l(g) = g + 1. Let f be l®. Solve -2*s = -4 - f for s.

5

Suppose 0 + 0 = -11*t. Solve 3*u = -t*u - 3 for u.

-1

Let m be (2 - 1)*(0 + 0). Suppose -2*s - 5*g = 3*s + 5, -s + 4*g = -4. Suppose s = 5*r - x - 125, 4*r - x - 100 = 3*x. Solve m = u - 6*u + r for u.

5

Let m(p) be the third derivative of -p6120 + 7*p560 + p43 + p36 - 9*p**2. Let s be (-2)/(-4) + 304. Let r be m(s). Solve -c + 2*c = r for c.

1

Suppose -w = -3*w + 32. Suppose -4*z - 13 - 3 = 0. Let j = w + z. Solve 0*m - j = 3*m for m.

-4

Suppose -3*p + 0 = -18. Solve p = -4*a - 2 for a.

-2

Let j = 11 + -15. Let t be -10*(1 + 6/j). Suppose t*o + 0 = 25. Solve o*h = -8 - 7 for h.

-3

Let l = -6 + 5. Let q be 8/(-1*l*2). Solve 2*y + 2 = q*y for y.

1

Let m(f) = -f3 - 7*f2 + 9*f + 10. Let g be m(-8). Solve -g*q = 3*q for q.

0